Gambaran Kejadian Kekerasan Pada Perempuan Dan Anak Di Wilayah Puskesmas Kasihan 1 Bantul Yogyakarta - luluk rosida; Luluk Khusnul Dwihestie; Nunung Ismiyatun (2021)
Violence is not only physical, but also psychic, socioeconomic and sexual violence that often goes unnoticed. In 2000, cases of violence in the world reached 1.6 people with the death toll reaching 28.8% per 100,000 people. 49.1% were caused by suicide and 31.3% as a result of homicide. Deaths from violence occur in developing countries at twice as many as developed countries. This research aims to know the characteristics in victims of violence in Puskesmas Kasihan I Bantul Yogyakarta. This type of research is quantitative with observational descriptive research design, retrospective approach. Sample technique is a total sampling of 32 respondents of victims of violence at Puskesmas Kasihan I Bantul Yogyakarta. Data collection using secondary data. Data analysis technique using univariate with frequency distribution. This study showed gender characteristics in victims of violence in Puskesmas Kasihan I Bantul Yogyakarta Year 2020, showing that Women were the most victims of violence as many as 21 people (65.6%). The age characteristics of the most victims of violence in the 30-39 year old category were 12 people (37.5%). The most educational characteristics of victims of violence in the category of High School Education were 11 people (34.4%). The job characteristics of the victims of violence were 8 people or 25% students and Housewives and other services as many as 7 people or 21.9% each. The characteristics of the marital status of the victims of violence are the most married or married, as many as 17 people (53.1%). For Puskesmas Kasihan I Bantul Yogyakarta is expected to continue to improve efforts to deal with and mentor victims of violence in the local area.